Technological capabilities, entrepreneurship and innovation of technology-based start-ups: The resource-based view - Seungku Ahn; Kwon-Sik Kim; Kwang-Hoon Lee (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Despite large-scale financial support of the government, there is increasing criticism about the inefficiency of public R&D investment that fails to lead directly to technological innovation of technology-based start-ups. This paper analyzes the factors that influence technological innovation in Korean technology-based start-ups based on the resource-based view (RBV). The empirical analysis combines ordinary least squares and ordered probit analysis of data collected from 248 technology-based start-ups in Korea. The analysis results statistically confirm the effects of technological capabilities and entrepreneurship on technological innovation. First, a start-up's technological capabilities measured by patents and technological competitiveness have significant positive effects on technological innovation, while the effect of having an in-house R&D department for technological innovation is not significant. Second, entrepreneurship has a significant positive effect on the technological innovation of a start-up, and this positive effect has a moderating effect that further promotes the positive effect of technological competitiveness on technological innovation.
Keywords: 650; innovation; entrepreneurship; RBV; start-ups; technological capabilities